An Optimal Planning Method for Park IES Considering Life Cycle Carbon Cost - Rengcun FANG; Jie YANG; Kui ZHOU; Tao HUANG; Fengbo LV (Zhongguo dianli)
Integrated energy system (IES) is one of the effective ways to achieve the “dual carbon” goal, and its planning, construction and operation need to take into account economic costs and low-carbon benefits. In order to comprehensively evaluate the comprehensive IES benefits, a planning method is proposed that incorporates the carbon emission cost of energy and equipment in the life cycle process of manufacturing, transportation, operation into the optimization goal. A hourly simulation and optimization is carried out for a park IES, and an analysis is made on the influence of different carbon cost scenarios on the IES optimal configuration and operation schemes. The proposed method can provide a reference for IES design and planning.